(untitled) (Revista de Administração, 2006)
The paper uses individual and organizational innovation adoption perspectives to analyze the factors that affected the adoption of Free Open Source Software by IT professionals from the University of São Paulo. Concepts from the Theory of Planned Behavior (AJZEN, 1991) and Hospitality Theory (CIBORRA, 1997) were useful for understanding and guiding managerial action that facilitated adoption of the technology. Training programs, technical support service and communities of practice, created by the University according to the Theories' precepts, contributed to the success of the process.